107 A decade after the Delaware-Oslo ACL treatment algorithm: What are the long-term outcomes?. (25th January 2023) - Urhausen, Anouk; Pedersen, Marie; Grindem, Hege; Ito, Naoaki; Arhos, Elanna; Schmith, Angela; Silbernagel, Karin; Axe, Michael; Engebretsen, Lars; Snyder-Mackler, Lynn; Risberg, May Arna
Abstract : Introduction: The Delaware-Oslo ACL treatment algorithm is distinct as it includes progressive rehabilitation with repeated functional testing, patient education and shared decision-making about treatment. We described and compared 10-year knee osteoarthritis and patient-reported outcomes in athletes who followed our treatment algorithm and chose early (<6 months) anterior cruciate ligament reconstruction (ACLR) with pre- and postoperative rehabilitation, delayed (>6 months) ACLR with pre- and postoperative rehabilitation, and progressive rehabilitation alone. Materials and Methods: We included 276 athletes with unilateral ACL injury from a prospective cohort. Tibiofemoral radiographs, the International Knee Documentation Committee (IKDC) and the Knee injury and Osteoarthritis Outcome Score (KOOS) subscales were assessed. Radiographic osteoarthritis was defined as Kellgren and Lawrence (K&L) grade ≥2 and symptomatic osteoarthritis as KOOS pain score ≤72 and K&L grade ≥2. Results: At 10 years, 138 athletes had interpretable radiographs, whereof 59% had chosen early ACLR, 14% delayed ACLR, and 27% progressive rehabilitation alone. Across treatment groups, 12% had radiographic osteoarthritis and 1% had symptomatic OA. The mean±SD IKDC score was 87±11 points, while the KOOS subscales ranged between 76±20 (quality of life) and 98±4 (activities of daily living) points. The KOOS sport and recreation score was statistically significantly lower following delayed ACLR compared to early ACLR (p=.002) or rehabilitation alone (p=.004). No other outcomes differed between groups (p>.2). Conclusion: Patients with ACL injuries who followed our treatment algorithm had low rates of knee osteoarthritis and good patient-reported outcomes at 10 years. Our findings reflect outcomes after treatment as it occurs in clinical practice.